GEOCHEMICAL CHAOS: PERIODIC AND NONPERIODIC GROWTH OF MIXED-LAYER PHYLLOSILICATES - Wang Y.; Xu H. (My University, 2006)
Interstratification-periodic or nonperiodic stacking of two different silicate layers along a c*-axis-is common in phyllosilicates. Published evidence indicates that some interstratified minerals precipitate directly from aqueous solutions. In this paper, we have demonstrated, based on chaos theory, that both periodic and nonperiodic interstratification can autonomously arise from simple kinetics of mineral growth from a solution. Growth of a mixed-layer mineral is assumed to proceed layer by layer, and each layer starts with the formation of a base (Si, Al)-O tetrahedral sheet, whose structural configuration in a-b dimensions determines the type of new layer that forms. The sequence of layer stacking can be described by a one-dimensional map (i.e., a difference equation), which accounts for two competing factors: (1) the affinity of each end-member structural component for attaching to the surface of the preceding layer, and (2) the strain energy created by stacking next to each other two silicate layers with different structural configurations. Chaotic (or nonperiodic) interstratification emerges when the contacting solution becomes slightly supersaturated with respect to both structural components. The transition from one interstratification pattern to another reflects a change in chemical environment during mineral crystallization. Our model can successfully predict the occurrence of mixed-layer phyllosilicates and the associated layer stacking sequences observed in both hydrothermal alteration and sediment diagenesis. The model suggests that the diagenetic transition of smectite ? nonperiodic illite/smectite ? ordered illite/smectite ? illite may reflect relative changes in the saturation degree of pore water with respect to two end-member phases as a result of increasing burial temperatures. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CRYSTALLIZATION; DIAGENESIS; GEOCHEMISTRY; HYDROTHERMAL ALTERATION; MINERALOGY; PHYLLOSILICATE; STRAIN; STRATIFICATION